PNPLA3 gene predicts clinical recovery after sustained virological response in decompensated hepatitis C cirrhosis. Issue 1 (12th March 2019) - Dunn, Winston; Vittal, Anusha; Zhao, Jie; He, Jianghua; Chakraborty, Shweta; Whitener, Melissa; Fohn, Sara; Ash, Ryan; Taylor, Ryan M; Olyaee, Mojtaba; Olson, Jody C; Todd, Nancy; et al.
Abstract : Background: Patients with decompensated hepatitis C virus (HCV) cirrhosis experience various outcomes after sustained virological response (SVR), ranging from clinical recovery to further deterioration. We hypothesised that the genetic risk for steatosis, namely the polymorphisms rs738409 of Patatin-like Phospholipase Domain-Containing 3 ( PNPLA3 ), rs58542926 of Transmembrane-6-Superfamily-2 ( TM6SF2 ), and rs641738 of Membrane-bound O-acyltransferase Domain-Containing 7 ( MBOAT7 ), is predictive of recovery. Methods: We prospectively enrolled 56 patients with Child-Pugh (CPT) B/C cirrhosis who underwent antiviral therapy. The primary outcome was change in CPT score at 12, 24, and 48 weeks after SVR. We used a linear mixed-effects model for analysis. Results: Forty-five patients ( PNPLA3 : 21 CC, 19 CG, 5 GG) survived to the first endpoint without liver transplantation. The mean change in CPT score at 12, 24, and 48 weeks was −1.57 (SE=0.30), –1.76 (SE=0.32), and −2.0 (SE=0.36), respectively, among the patients with the PNPLA3 CC genotype and −0.50 (SE=0.20), –0.41 (SE=0.25), and −0.24 (SE=0.27), respectively, among the other 24 patients. After adjustment for baseline characteristics, the PNPLA3 CG/GG genotypes were associated with a 1.29 (SE=0.30, p<0.0001) point higher CPT score. Most of the difference came from differences in hepatic encephalopathy and bilirubin. The results for rs58542926 and rs641738 were not significant. Conclusion: The PNPLA3 CG/GG genotypes could identify a subgroup of patients with decompensated HCV cirrhosis that had suboptimal clinical recovery despite SVR. An understanding of the genetic factors that influence clinical outcomes will help target patients for liver transplant based on individual genetic risk factors and provide insight leading to new therapeutic approaches.